First record of Loisirella Holzinger, Holzinger & Egger, 2013 and description of a new species from Brazil (Hemiptera: Fulgoromorpha: Cixiidae) - Viegas, Eduarda Fernanda Gomes; Ale-Rocha, Rosaly; Takiya, Daniela Maeda (Zootaxa, 2021)
A second species of the genus Loisirella Holzinger, Holzinger & Egger, 2013, L. xanthosa sp. nov., is described from Amazonas State, Brazil. The new species can be distinguished from L. erwini Holzinger, Holzinger & Egger, 2013, type species of the genus, by the coloration of the body and wing and male genitalia. This species represents the first record of Loisirella from Brazil.